Oriented porphyrin grafted polyether sulphone membrane for multi-ion screening and preparation method of orientated porphyrin grafted polyether sulphone membrane

By utilizing the functionalized polymer DPAES-g-TAPP and a voltage-gated energy barrier regulation mechanism, the problem of insufficient precision in multivalent ion sieving and dynamic regulation of existing ion separation membranes is solved, achieving efficient and low-cost multivalent ion gradient sieving, which is suitable for seawater desalination and metal recovery.

CN121360490APending Publication Date: 2026-01-20JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511795964.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-02
Publication Date
2026-01-20

AI Technical Summary

Technical Problem

Existing ion separation membranes have shortcomings in terms of multivalent ion sieving and dynamic control precision, making it difficult to achieve efficient and accurate separation of multiple ions. Furthermore, their preparation processes are complex and costly, limiting their industrial application.

Method used

We designed a functionalized polymer, DPAES-g-TAPP, and prepared oriented ultrathin films by water surface spreading. We then used a voltage-gated energy barrier control mechanism to achieve continuous gradient sieving of multivalent ions.

Benefits of technology

It achieves high-precision gradient sieving of multivalent ions, significantly improves dynamic control accuracy and response speed, simplifies the process and reduces costs, and is suitable for industrial applications such as seawater desalination and metal recovery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121360490A_ABST
    Figure CN121360490A_ABST
Patent Text Reader

Abstract

The invention discloses an oriented porphyrin grafted polyether sulphone membrane for multi-ion screening and a preparation method thereof, and belongs to the technical field of ion separation membranes, polyether sulphone is used as a matrix, selective binding sites are introduced by grafting porphyrin molecules, and an ultrathin membrane is prepared by adopting a water surface expansion method, and the method is more efficient than a traditional casting method, and has good application prospects. According to the preparation method, porphyrin is taken as a carrier, an ordered structure is formed, the uniformity and selectivity of the membrane are improved, ion screening under gradient voltage is realized through the binding energy difference between different ions and porphyrin, and high-valence ions such as Fe and Al can be separated in sequence; according to the preparation method, Mg < 2 + > / Ca < 2 + > selectivity is improved, an energy barrier is directly regulated and controlled through voltage, millisecond-level response is achieved, the process is simplified, large-scale production is achieved, the core bottleneck of an existing ion screening membrane on multivalent separation, dynamic regulation and control and expandability is effectively solved, and a new normal form is provided for high-precision ion separation.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of ion separation membranes, and particularly relates to an oriented porphyrin grafted polyarylether sulfone membrane for multi-ion sieving and a preparation method thereof. BACKGROUND

[0002] Ion separation membrane materials are a kind of functional materials that realize ion selective separation by regulating pore size, charge or chemical affinity, mainly including three categories of polymer-based, inorganic-based and composite membranes. Polymer-based materials such as perfluorosulfonic acid membranes, polyamide and polyvinylidene fluoride have high ion conductivity and processability, and are widely used in fuel cells, reverse osmosis desalination and wastewater treatment; inorganic materials such as ceramic membranes, zeolite molecular sieves and graphene membranes are suitable for gas separation or lithium extraction in harsh environments due to their high temperature resistance, corrosion resistance and precise sieving characteristics. In recent years, hybrid organic-inorganic membranes, metal-organic frameworks and two-dimensional materials (such as MXene) have significantly improved ion selectivity and flux through structural optimization, and bio-based materials (such as chitosan) have attracted attention due to their environmental characteristics. The performance of such materials depends on ion selectivity and chemical stability, and has important application value in energy conversion (flow battery), water treatment (electrodialysis) and chemical separation, and is a research hotspot in the development of membrane science and technology.

[0003] Voltage-gated MXene membrane (Dalian University of Technology, 2024), by modifying MXene nanosheets with polydopamine, constructing channels at the angstrom level, and introducing high-charge cations (such as Mg 2+ ) to regulate the ion distribution at the channel entrance. When a voltage is applied, the electric double layer in the channel reorganizes, preferentially selecting K + (K + / Li + selectivity of 40.9, and achieving an on-off ratio of 9.912. The main implementation principle is: voltage-induced ion dehydration and energy barrier reduction, combined with Mg 2+ controlled entrance charge distribution, to enhance the selectivity of target ions.

[0004] Light-gated intelligent ion sieving membrane (Zhou Zongyao team of Harbin Institute of Technology, 2024), based on conjugated microporous polymers, realizes the hierarchical sieving of hydrogen, potassium, sodium and other ions by regulating the reversible change of pore size through photoisomerization. The main implementation principle is: photoresponsive molecular chain isomerization leads to dynamic adjustment of pore size, for example, ultraviolet light triggers pore size shrinkage, and visible light restores the open state.

[0005] Existing ion separation membranes achieve multi-level and multi-valence state of ions based on the physical and chemical properties of ions, and there are great challenges in the accuracy of distinguishing between same / valence and different / valence.

[0006] For example, the following three ion separation mechanisms: The separation of ions by pore size, including the distinction between the naked ion radius and the hydrated radius. First, the size difference of each ion radius is in the order of angstrom, and the difference of such distinction is very small. Second, the separation of ions by pore size requires extremely strict pore precision of the material, and the preparation of most materials is difficult to achieve.

[0007] The separation of ions by the charge and valence of ions. First, the valence of common ions ranges from monovalent to trivalent, and the maximum difference of their charge is only about three times — this relatively small charge span itself makes it difficult to effectively distinguish ions with the same charge; and for ions with the same charge (such as Mg²⁺ and Ca²⁺ both as divalent, Li⁺ and Na⁺ both as monovalent), since the key distinction of “charge difference” is lost, the difficulty of distinguishing them is significantly increased. For this reason, current researches often achieve ion separation through electrostatic effects, i.e., using the selective permeation of materials to different electrically charged ions (only allowing ions opposite to the surface charge of the material to pass) to preliminarily screen ions. But this method can only achieve the rough separation of “different electrically charged ions”, and cannot solve the problem of distinguishing “ions with the same electric property (especially the same charge)”, resulting in obvious limitations in the selectivity of ion separation.

[0008] The separation of ions by dielectric repulsion effect. This effect ignores the charge property of ions, and is only related to the charge amount of ions. The dielectric effect is often used to explain the separation between monovalent and multivalent ions, and this effect only exists at the interface of the material, which is difficult to control and complex, so few researchers specially prepare materials to separate ions by this effect.

[0009] The ion separation membranes studied in the laboratory still face challenges in large-scale production. The difficulty of material preparation, cost, stability of the material, and recovery rate are all factors that affect its market application. Specifically, the current mainstream biomimetic materials (such as biological channel proteins and metal organic frameworks MOFs) often rely on complex synthesis processes, and some also require high-cost equipment support (such as the cryo-EM structure analysis of biological channel proteins), which is naturally difficult to adapt to mass production; while the MXene membrane shows potential in separation performance, but its preparation needs to be achieved by stacking nanosheets layer by layer, which not only has a long and time-consuming process, but also has the problem of low product yield, further limiting its industrial application.

[0010] The existing ion separation membranes also face the problem of insufficient dynamic regulation accuracy: the switch ratio of traditional voltage or light-controlled membranes is low (such as the switch ratio of the MXene membrane mentioned in the previous example is only 9.9), and the response speed is slow (such as the light-controlled membrane needs to respond for minutes), which cannot accurately control the starting voltage and flux of ion transmission.

[0011] Traditional membranes are difficult to effectively distinguish ions with similar physicochemical properties (such as ionic radius, charge density) (for example, Mg²⁺ and Ca²⁺), and cannot achieve gradient screening of multiple ions (i.e., sequentially separating ions of different valence or binding capacity) by a single device.

[0012] The prior art relies on size screening or electrostatic effects, but the separation efficiency is significantly reduced when facing ions of the same valence or similar size. Competitive binding sites cause ions to form similar complexes, further weakening selectivity.

[0013] Current materials, such as metal / covalent organic frameworks, layered materials, have problems such as difficult preparation, easy swelling or pollution, and difficulty in scaling, which limit their practical application. For example, the preparation process of interfacial polymerization requires a large amount of solvent, has high preparation cost, and the film is difficult to recover after film formation, which limits its market development.

[0014] Ion channels in biological systems rely on voltage gating to achieve precise control of ion flow. The design and application of the existing technology thin film gating system generally lack precision, thus limiting the intelligent application scenarios of the thin film. SUMMARY

[0015] To solve the above problems, the present application designs a functional polymer (DPAES-g-TAPP), prepares an oriented ultra-thin film by a water surface spreading method, and uses a voltage gating energy barrier regulation mechanism to achieve continuous gradient screening of multivalent ions.

[0016] An oriented ion separation membrane for multi-ion screening, which is formed by an ultra-thin film of a polyarylether sulfone polymer grafted with porphyrin molecules, and the porphyrin molecules are arranged in an oriented manner in the film; the separation membrane can respond to different applied voltages to enable Fe³⁺, Al³⁺, Mg²⁺, Ca²⁺, Cu²⁺ and Li⁺ ions to be sequentially activated for transmission, thereby realizing gradient screening of multivalent ions.

[0017] Further, the thickness of the ultra-thin film is 20-50 nm.

[0018] Further, the porphyrin molecules are tetra(4-aminophenyl)porphyrin.

[0019] Further, the polyarylether sulfone backbone contains double acryl side groups.

[0020] Further, the on-off ratio of the separation membrane is greater than 10 3 .

[0021] Further, the difference in the starting voltage of Fe³⁺ and Li⁺ is 10 3 above, or the selectivity of Mg 2+ / Ca 2+ is greater than 50.

[0022] A method for preparing an oriented ion separation membrane for multi-ion sieving, comprising the following steps: The porphyrin is grafted to a polyarylether sulfone polymer to form a polymer solution in an organic solvent; the polymer solution is added dropwise to the surface of water; the polymer solution is spread on the surface of water by the Marangoni effect to form a liquid film; and the organic solvent is volatilized to obtain a membrane with an oriented structure.

[0023] Further, the concentration of the polymer solution is 10-50 mg / mL, the dropwise volume of the polymer solution is 5-50 muL, and the temperature of the water surface is 20-40 DEG C.

[0024] Further, the organic solvent is dichloromethane or chloroform.

[0025] The use of an oriented ion separation membrane for multi-ion sieving under a gradient voltage for separating target ions from a mixed solution containing at least two kinds of ions of Fe3+, Al3+, Mg2+, Ca2+, Cu2+ and Li+.

[0026] The beneficial effects of the present application are: The voltage-gated step-by-step continuous gradient sieving of multiple different valence ions is realized. 3+ , Al 3+ , Mg 2+ , Ca 2+ , Cu 2+ , Li + and other ions are sequentially opened for transmission according to the starting voltage (0.07 mV to 250 mV), and the difference in starting voltage reaches 104 orders of magnitude, breaking through the limitation of traditional membranes that only separate 1-2 kinds of ions.

[0027] The ordered ultrathin film structure is designed to improve ion permeability and selectivity, the water surface spreading method (Marangoni effect induced molecular orientation) is used to prepare a 20 nm thick homogeneous membrane, and the parallel arrangement of porphyrin molecules is ensured to form a directional ion channel, so that the selectivity of Mg 2+ / Ca 2+ is improved to more than 50.

[0028] The dynamic control precision and response speed are improved, the energy barrier is directly regulated by voltage according to the difference in porphyrin-ion binding energy, and millisecond-level response is realized, and the on-off ratio is more than 10 3 , which is significantly better than the prior art.

[0029] Simplify the process and realize the scale, replace the traditional multi-layer stacking or biological template method with one-step interface self-assembly (water surface expansion method), shorten the film forming time to seconds, and the thin film can be prepared again by dissolving the solution. Provide a low-cost solution for industrial seawater desalination and metal recovery. Through the above technical scheme, the present application effectively solves the core bottleneck of the existing ion sieve membrane in multivalent separation, dynamic control and scalability, and provides a new paradigm for high-precision ion separation. BRIEF DESCRIPTION OF DRAWINGS

[0030] Figure 1 For the synthesis steps of the grafted porphyrin polymer.

[0031] Figure 2 For the nuclear magnetic resonance spectrum of the polyarylether sulfone with olefin-containing side chains.

[0032] Figure 3 For the scanning electron microscope and transmission electron microscope images of the DPAES-g-TAPP ultra-thin film prepared by the water surface expansion method.

[0033] Figure 4 For the starting voltage of the grafted porphyrin polymer film to different ions.

[0034] In the figure: 1 the first characteristic peak of H on the benzene ring, 2 the second characteristic peak of H on the benzene ring, 3 the third characteristic peak of H on the benzene ring, 4 the fourth characteristic peak of H on the benzene ring, 5 the fifth characteristic peak of H on the benzene ring, 6 the first characteristic peak of propylene group H, 7 the second characteristic peak of propylene group H. DETAILED DESCRIPTION

[0035] Material design and synthesis Functional polymer synthesis: polyarylether sulfone (DPAES) is used as the main chain, double acryl side groups are introduced through nucleophilic polycondensation reaction, double acryl side groups are oxidized into epoxy groups, and then tetra (4-aminophenyl) porphyrin (TAPP) is grafted through click chemistry amination reaction to form DPAES-g-TAPP polymer. Porphyrin molecules act as ion binding sites, and the central cavity and amino functional groups can selectively complex metal ions.

[0036] Ultra-thin film preparation process Water surface expansion method: the polymer DPAES-g-TAPP is dissolved in dichloromethane (concentration 20 mg / mL), the polymer solution is added dropwise to the water surface, and the Marangoni effect is used to drive the droplet to spread quickly, forming an ultra-thin film. The process advantage lies in the rapid film formation and molecular orientation structure, which only takes a few seconds from droplet spreading to solvent evaporation, much faster than the traditional casting method (which takes several hours). The interface effect induces the parallel arrangement of porphyrin molecules to form a directional ion transport channel. Thickness control: by adjusting the solution concentration and drop volume, the thickness in the range of 20 nm and above can be accurately controlled.

[0037] Voltage-gated ion sieving mechanism Binding energy differences: The complexation ability of different ions with porphyrins varies significantly (e.g., Fe³⁺ binding energy > Li⁺), resulting in different energy barriers required for transport.

[0038] Voltage-driven: When a voltage is applied, ions must overcome an energy barrier to enter the channel. Ions with higher binding energies (such as Fe³⁺) require a lower initial voltage (0.07 mV).

[0039] Gradient sieving achieves this: from low voltage to high voltage, the membrane sequentially allows Fe... 3+ Al 3+ Mg 2+ Ca 2+ Cu 2+ Li + This enables multi-ion gradient separation.

[0040] Ion transport properties: for example, thin films in the presence of Fe 3+ At the time, not through Li + Ions, K + Ions and Li + Ion selectivity up to 3900, onset voltage range: Fe 3+ (0.07 mV) to Li + (250 mV), spanning 10 4 Order of magnitude, drive voltage switching ratio: >10 3 It is significantly superior to MXene membrane (on-off ratio 9.9).

[0041] Application scenarios: seawater desalination, metal recycling, biomimetic devices, etc.

[0042] Materials Synthesis and Characterization Synthesis of dipropylene-side-group polyarylene ether sulfones (DPAES) Under nitrogen protection, diallyl bisphenol A (DBA), 4,4'-dihydroxybiphenyl (DBP), 4-fluorophenyl sulfone (DPS), anhydrous potassium carbonate (K2CO3), dimethylacetamide (DMAc), and toluene were added to a three-necked flask and stirred until completely dissolved. The mixture was then refluxed at 135°C for 2.5 hours for dehydration. After dehydration, the temperature was raised to 165°C to remove excess toluene. After complete removal of toluene, the reaction continued for 3 hours until the reaction solution became viscous. The hot viscous solution was poured into acidic deionized water, precipitating white polymer strips. After standing overnight, the strips were pulverized into polymer particles using a high-speed pulverizer, and then washed three times each with boiling deionized water and ethanol. After drying, polyarylether sulfone (DPAES) was obtained.

[0043] Characterization: Nuclear magnetic resonance hydrogen spectrum (1H NMR): δ 6.8-7.2 ppm (aromatic ring H), δ 5.8-6.2 ppm (propylene double bond H).

[0044] Gel permeation chromatography (GPC): Mn=75.9 kDa.

[0045] Synthesis of epoxy group grafted polymer (DPAES-g-PO) Step: 3 g of polyarylether sulfone (DPAES) was dissolved in 30 mL of dichloromethane solvent, stirred at room temperature until completely dissolved, and then placed in an ice water bath for cooling; another 4.36 g of meta-chloroperoxybenzoic acid (mCPBA) was dissolved in 40 mL of dichloromethane solvent, and after cooling, it was slowly added to the above cooled polymer solution, reacted in an ice water bath for 2 hours, and then gradually warmed to room temperature for continued reaction for 30 hours; after the reaction was completed, the reaction mixture was poured into 400 mL of absolute ethanol, and after standing, the white fibrous solid was filtered; the solid was redissolved in 20 mL of dichloromethane, and then precipitated in ethanol again, and after drying, the polyarylether sulfone containing epoxy side groups (DPAES-g-PO) was obtained.

[0046] Characterization: Infrared spectrum (FT-IR): 910 cm⁻¹ (epoxy group characteristic peak).

[0047] Synthesis of porphyrin grafted polymer (DPAES-g-TAPP) Step: 500 mg of polyarylether sulfone containing epoxy side groups (DPAES-g-PO) was dissolved in an appropriate amount of dimethylacetamide, 147.5 mg of tetra(4-amino phenyl) porphyrin was added, and reacted at 100°C for 2 hours; after the reaction was completed, the reaction mixture was added to ethanol for precipitation, the obtained solid was collected, dissolved in a small amount of dichloromethane, and then precipitated in ethanol again, and after drying, the final product porphyrin grafted polyarylether sulfone (DPAES-g-TAPP) was obtained.

[0048] Characterization: Ultraviolet-visible spectrum (UV-Vis): 418 nm (porphyrin Soret band), confirming successful grafting of TAPP.

[0049] X-ray diffraction (XRD): 2θ=25.6° (π-π stacking peak), indicating ordered arrangement of molecules.

[0050] Ultra-thin film preparation process Solution preparation: DPAES-g-TAPP was dissolved in dichloromethane with a concentration of 20 mg / mL, and ultrasonically dispersed for 30 minutes.

[0051] Droplet spreading: 16.7 μL solution was dropped onto the surface of deionized water (temperature 25℃, humidity 50%) using a microsyringe.

[0052] Marangoni effect driven film formation: The tension difference between dichloromethane (27.2 mN / m) and water (72.0 mN / m) induced rapid spreading, forming a liquid film with a diameter of about 5 cm. Shear flow induced the parallel arrangement of porphyrin molecules to the water surface.

[0053] Solvent evaporation and orientation solidification: Dichloromethane was completely volatilized in 10 seconds, and the polymer chains were tightly stacked through π-π interaction, forming a homogeneous film with a thickness of 20 nm.

[0054] Process parameter control: Film thickness adjustment: Precise control by solution concentration (10-50 mg / mL) and drop volume (5-50 μL).

[0055] Orientation degree optimization: The water temperature was controlled at 20-30℃ to avoid turbulent flow destroying the molecular arrangement. The central cavity of porphyrin (diameter about 0.35 nm) only allows dehydrated ions to pass through.

[0056] Energy barrier regulation: Binding energy difference: the binding energy of Fe³⁺ and porphyrin is -120 kJ / mol, and that of Li⁺ is -40 kJ / mol (DFT calculation). Low voltage (0.07 mV): Fe³⁺ binding energy is high, which preferentially overcomes the energy barrier to pass through the film. High voltage (250 mV): Li⁺ requires higher voltage to drive, realizing separation.

[0057] Fe³⁺ / Li⁺ separation performance test Test conditions: Film: DPAES-g-TAPP film prepared by water surface spreading method (thickness 20 nm).

[0058] Solution: 0.001 M FeCl3 and LiCl mixed solution (1:1).

[0059] Equipment: Keithley 6487 picoammeter, Ag / AgCl electrode.

[0060] Test steps: The voltage was gradually increased from 0 to 500 mV, and the current change was recorded.

[0061] Results: The starting voltage of Fe³⁺ is 0.07 mV, and that of Li⁺ is 250 mV, with a separation factor >1000.

[0062] The present application realizes high-precision gradient screening of multivalent ions through the three-in-one technical path of molecular design, interface self-assembly, and voltage regulation.

[0063] The core innovation points include: Functional polymer synthesis: precise grafting of porphyrin through click chemistry to form selective binding sites.

[0064] Ultra-thin film controllable preparation: water surface spreading method realizes 20 nm thickness and molecular orientation regulation.

[0065] Voltage gating mechanism: energy barrier grading driven by binding energy difference, breaking through the traditional screening limit.

[0066] Key points include: 1. Design of functional polymer: using polyarylether sulfone as the matrix, introducing selective binding sites by grafting porphyrin molecules, which is the core material innovation, because the introduction of porphyrin directly affects the ion selectivity and binding energy difference.

[0067] 2. Water surface spreading method for preparing ultra-thin film: using the Malan-Goni effect and shear flow to realize molecular orientation arrangement, this method is more efficient than traditional casting method, forming ordered structure, improving the uniformity and selectivity of the film.

[0068] 3. Voltage gating mechanism: through the binding energy difference of different ions and porphyrin, realizing ion screening under gradient voltage, which involves the regulation of energy barrier, is the core principle of the technical scheme.

[0069] 4. Multivalent ion gradient separation: can sequentially separate Fe³⁺, Al³⁺ and other high valence ions, which is difficult to achieve by existing technology, and belongs to a significant technical breakthrough.

[0070] Key innovation points Design of functional polymer (DPAES-g-TAPP) Through click chemistry amination reaction, tetra(4-aminophenyl)porphyrin is grafted to the polyarylether sulfone backbone to form a functional material with ion selective binding sites.

[0071] Water surface spreading method for preparing oriented ultra-thin film Using the Malan-Goni effect and shear flow to induce molecular arrangement, realize the directional arrangement of porphyrin molecules parallel to the water surface, form an ordered ultra-thin film with a thickness of only 20 nm. The voltage gating energy barrier regulation mechanism is based on the binding energy difference of porphyrin-ion (such as Fe³⁺ binding energy > Li⁺), by applying gradient voltage to sequentially open the transmission channel of different ions, the initial voltage span reaches 10 4 orders of magnitude. The single membrane device realizes the continuous gradient separation of multivalent ions Fe³⁺→Al³⁺→Mg²⁺→Ca²⁺→Cu²⁺→Li⁺ as needed, breaking through the limitation of traditional membrane only separating 1-2 kinds of ions.

[0072] Realize the continuous gradient separation of multivalent ions Prior art disadvantages: conventional membranes (such as MXene membranes, light-controlled membranes) can only separate 1-2 ions (such as K⁺ / Li⁺), and cannot handle multivalent ions (such as Fe³⁺, Al³⁺, Mg²⁺).

[0073] Invention solution: through porphyrin functionalization and voltage gating mechanism, ions are driven to transmit in gradient of initial voltage (0.07 mV to 250 mV) according to energy difference.

[0074] Experimental data support: The initial voltage span reaches 10 4 orders of magnitude (Fe³⁺: 0.07 mV, Li⁺: 250 mV).

[0075] The selectivity for Mg²⁺ / Ca²⁺ is more than 50, far exceeding that of conventional membranes (<10).

[0076] Dynamic control precision and response speed are significantly improved Prior art disadvantages: MXene membrane switch ratio is only 9.9, and light-controlled membrane response speed is slow (minute level).

[0077] Invention solution: voltage directly controls porphyrin-ion binding energy barrier, with millisecond-level response.

[0078] Experimental data support: The switch ratio is >10³, which is 100 times higher than that of MXene membrane.

[0079] Membrane structure order is greatly improved Prior art disadvantages: the membrane prepared by casting method has low selectivity (Mg²⁺ / Ca²⁺ selectivity <10) due to disordered structure.

[0080] Invention solution: water surface spreading method (Marangoni effect) induces parallel arrangement of porphyrin molecules, forming a homogeneous ultrathin film.

[0081] Experimental data support: the membrane thickness is 20 nm, the surface roughness is only 2 nm, and the periodic arrangement of 0.35 nm is displayed, proving the ordered stacking of molecules.

[0082] Process simplification and cost reduction Prior art disadvantages: MXene membrane requires layer-by-layer stacking of nanosheets, and the process is complex; the synthesis cost of biomimetic membrane is high.

[0083] Invention solution: one-step water surface spreading method (without complex equipment), film formation time is shortened to seconds.

[0084] Experimental data support: film formation time is <10 seconds, while traditional casting method takes several hours.

[0085] High flux and anti-fouling ability Prior art disadvantages: flux decay due to channel blockage of MOFs membrane Invention solution: ultra-thin (20 nm) ordered structure reduces transmission resistance, and porphyrin-ion combination reduces membrane fouling.

[0086] Experimental data support: Fe³⁺ flux retention rate > 90% after 24 hours of continuous operation.

[0087] The invention surpasses the prior art in ion separation efficiency, dynamic control precision, process cost and large-scale capacity through the synergistic innovation of functional polymer design, interface self-assembly process and voltage gating mechanism, and provides a revolutionary solution for seawater desalination, metal recovery and other fields. The invention has been fully proven to be feasible and superior through systematic experimental verification, theoretical simulation and performance testing, and the specific data and results are as follows: Functional polymer synthesis verification, route as Figure 1 shown.

[0088] Synthesis of double acryl side group polyarylether sulfone (DPAES): DPAES was prepared by nucleophilic polycondensation reaction, and characterized by nuclear magnetic resonance hydrogen spectrum (¹H NMR) (Figure Figure 2 ), characteristic peaks of aromatic ring hydrogen atoms appeared at δ 6.8-7.2 ppm, and characteristic peaks of propylene double bond hydrogen atoms appeared at δ 5.8-6.2 ppm, confirming the successful introduction of double acryl side groups into the polyarylether sulfone main chain.

[0089] Synthesis of epoxy group grafted polymer (DPAES-g-PO): m-chloroperbenzoic acid (mCPBA) was used to oxidize the double acryl side groups of DPAES.

[0090] Synthesis of porphyrin grafted polymer (DPAES-g-TAPP): tetra(4-aminophenyl) porphyrin (TAPP) was grafted to DPAES-g-PO through click chemistry amination reaction.

[0091] Feasibility verification of ultra-thin membrane preparation DPAES-g-TAPP ultra-thin membrane was prepared by water surface spreading method, and characterized by scanning electron microscope (SEM) and transmission electron microscope (TEM), as shown in Figure 3 ; (a) Electron microscope photo of grafted porphyrin polymer membrane (b) Electron microscope photo of cross section of grafted porphyrin polymer membrane (c) Transmission electron microscope photo of grafted porphyrin polymer membrane, and (d) Chain segment spacing.

[0092] SEM images show that the film surface is uniform and defect-free, with a cross-sectional thickness of approximately 20 nm. Compared with the traditional casting method (thickness 200 nm), the ultrathin structure significantly reduces ion transport resistance. TEM images and selected area electron diffraction patterns show that there is an ordered structure with a period of 0.35 nm inside the film, corresponding to the π-π stacking spacing of porphyrin molecules. This confirms that the water surface unfolding method successfully induces the parallel orientation of porphyrin molecules through the Marangoni effect and shear flow, forming directional ion channels. The film formation process can stably achieve the structural requirements of "molecular orientation-ultrath thin homogeneity".

[0093] Performance testing (feasibility of ion sieving function) Voltage-gated gradient screening performance The ion transport performance of the membrane was tested using a Keithley 6487 semiconductor picoammeter paired with a custom Ag / AgCl electrode in a chloride salt solution without a salt gradient. The results are as follows: Single-ion transport verification: In a 0.001 mol / L FeCl3 solution, when a voltage of 0.07 mV is applied, the current jumps from the baseline (<1×10⁻¹² A) to 1×10⁻¹² A. 9 A indicates that Fe³⁺ begins to permeate through the membrane; in LiCl solution of the same concentration, a voltage of 250 mV is required for a significant current response, and the initial voltage difference between Fe³⁺ and Li⁺ reaches 10 mV. 4 The magnitude of the difference confirms that the membrane exhibits significant voltage-gated selectivity for different ions.

[0094] Separation verification of a multi-ion mixed system: In a 0.001 mol / L mixed solution of FeCl3, AlCl3, MgCl2, CaCl2, CuCl2, and LiCl, the voltage was gradually increased from 0: only Fe³⁺ transmission signal was detected at 0.07 mV, Al³⁺ signal appeared at 0.3 mV, Mg²⁺ signal appeared at 0.7 mV, Ca²⁺ signal appeared at 0.9 mV, Cu²⁺ signal appeared at 4.2 mV, and Li⁺ signal appeared at 250 mV. The ion transmission sequence was completely consistent with the design expectation of "Fe³⁺→Al³⁺→Mg²⁺→Ca²⁺→Cu²⁺→Li⁺", realizing continuous gradient sieving of multivalent ions and breaking through the limitation of traditional membranes that can only separate 1-2 types of ions. Figure 4 ).

[0095] High valence ion and low valence ion separation factor: in a 0.001 mol / L FeCl3 and LiCl mixed solution, the Fe³⁺ / Li⁺ separation factor is >1000, and the ion flux retention rate of the membrane remains >90% after 24 hours of continuous operation, proving that the membrane has excellent anti-pollution ability and long-term stability, meeting the continuous operation requirements in actual applications.

[0096] Dynamic regulation performance 1. Response speed: through step voltage test, the current response time of the membrane to voltage change is <1 second (millisecond level), which is much faster than existing light control membranes (minute level response), and can realize fast switching control of ion transmission.

[0097] 2. On-off ratio: in a 0.001 mol / L FeCl3 solution, the ratio of the on current (0.07 mV) to the off current (0 mV) of the membrane (on-off ratio) is >10³, which is significantly better than the voltage-gated MXene membrane reported by Dalian University of Technology (on-off ratio 9.9), and the dynamic regulation accuracy is greatly improved.

[0098] The present application proves through a complete verification system of "material synthesis - structure characterization - performance test - theoretical simulation": 1. The synthesis process of functionalized polymers (DPAES, DPAES-g-PO, DPAES-g-TAPP) is stable, and the product structure and purity meet the design requirements; 2. The water surface spreading method can efficiently prepare a 20 nm ultra-thin homogeneous membrane with directional porphyrin channels, and the membrane forming process has high repeatability; 3. The voltage-gated gradient separation performance, selectivity, dynamic response speed and long-term stability of the membrane to multivalent ions are better than existing technologies, the theoretical simulation is highly consistent with the experimental results, fully proving the feasibility and superiority of the technical scheme of the present application in practical applications, which can meet the needs of seawater desalination, metal recovery, and biomimetic devices.

[0099] Material alternative Main chain polymer replacement Alternative: use other rigid main chain polymers (such as polyether ether ketone PEEK, polyimide PI) to replace polyarylether sulfone (PAES) and graft porphyrin side chains.

[0100] Technical effect: maintain molecular orientation ability while improving the thermal stability of the membrane (PI temperature resistance can reach 300°C).

[0101] Functional molecule replacement Alternative: replace porphyrin (TAPP) with other macrocyclic compounds (such as crown ether, porphine, cyclodextrin, calixarene, etc.).

[0102] Technical effect: Optimized selectivity for specific ions (e.g., K⁺), adapting to different application scenarios.

[0103] Blending modification Alternative: Incorporate nanomaterials (such as graphene quantum dots, MOF nanoparticles) into DPAES-g-TAPP to enhance film mechanical strength or electrical conductivity.

[0104] Technical effect: Graphene quantum dots (doping amount 5 wt%) can increase the tensile strength of the film by 40%, while maintaining ion selectivity.

[0105] Process parameter adjustment Solvent system optimization Alternative: Use solvents such as chloroform and benzene instead of dichloromethane.

[0106] Technical effect: Adjust the spreading speed by the surface tension of the solvent to control the film thickness (chloroform film thickness can reach 50 nm).

[0107] Interface type expansion Alternative: Spread the polymer solution at the oil-water interface (such as silicone oil / water), and use the density difference between the two phases to regulate the molecular arrangement direction.

[0108] Technical effect: High viscosity of silicone oil phase can slow down solvent evaporation, forming a more dense ordered structure.

[0109] Temperature gradient induction Alternative: Set up a temperature gradient on the water surface (such as cold end 25℃, hot end 40℃), and use thermal convection to enhance molecular orientation.

[0110] Technical effect: SAED shows that the π-π stacking distance is reduced from 0.35 nm to 0.33 nm, further improving the ion transmission rate.

[0111] Structural design change Multilayer composite film Alternative: Composite DPAES-g-TAPP ultra-thin film with a support layer (such as porous polytetrafluoroethylene PTFE) to enhance mechanical stability.

[0112] Technical effect: The breaking strength of the composite film is improved, which is suitable for high-pressure separation scenarios.

[0113] Patterned film design Alternative: Pre-arrange a patterned template on the water surface by micro-contact printing to induce polymer directional arrangement and form micro-channels.

[0114] Technical effect: Realize regional ion sieving (such as sieving Fe³⁺ on the left side of the film and sieving Li⁺ on the right side), which is suitable for integrated lab-on-a-chip.

[0115] Other applications of the invention Environmental governance Heavy metal ion selective removal: Utilize the voltage-gating property to selectively remove heavy metal ions (e.g. Cu 2+ , Fe 3⁺ ) from industrial wastewater. Energy field

[0116] Ion-selective battery separator: For lithium-sulfur batteries, suppress the polysulfide shuttle effect.

[0117] Biomedicine Drug controlled release system: By external voltage to regulate the membrane permeability, realize the timing and quantitative drug release.

[0118] Sensor Ion concentration detection: Use the voltage-current response characteristics of the membrane to construct an ion concentration sensor.

Claims

1. An oriented ion separation membrane for multi-ion sieving, characterized by, The separation membrane is an ultrathin membrane formed by grafting porphyrin molecules on a polyarylether sulfone polymer, and the porphyrin molecules are arranged in an oriented manner in the membrane; the separation membrane can respond to different applied voltages to enable Fe³⁺, Al³⁺, Mg²⁺, Ca²⁺, Cu²⁺ and Li⁺ ions to be sequentially activated for transmission, thereby realizing gradient screening of multivalent ions.

2. The separation membrane according to claim 1, characterized by The ultrathin membrane has a thickness of 20-50 nm.

3. The separation membrane according to claim 1, characterized by, The porphyrin molecules are tetra(4-aminophenyl)porphyrin.

4. The separation membrane according to claim 1, characterized by, The polyarylether sulfone main chain contains double acryl side groups.

5. The separation membrane according to claim 1, wherein The separation membrane has a switch ratio greater than 10 3 .

6. The separation membrane according to claim 1, wherein The initial voltage difference between Fe3+and Li+is 10 3 The above, or Mg 2+ / Ca 2+ The selectivity of the above is greater than 50.

7. A method for preparing the separation membrane according to claim 1, characterized by, The method comprises the following steps: The porphyrin-grafted polyarylether sulfone polymer is dissolved in an organic solvent to form a polymer solution; the polymer solution is added dropwise to the surface of water; the polymer solution is spread on the surface of water by means of the Marangoni effect to form a liquid film; and the organic solvent is volatilized to obtain a membrane with an oriented structure.

8. The method of claim 7, wherein, The concentration of the polymer solution is 10-50 mg / mL, the volume of the polymer solution to be added dropwise is 5-50 μL, and the temperature of the water surface is 20-40 ℃.

9. The method of claim 7, wherein, The organic solvent is dichloromethane or chloroform.

10. Use of a separation membrane according to claim 1 for multi-ion sieving under a gradient voltage, characterized in that, The method is used for separating target ions from a mixed solution containing at least two of Fe³⁺, Al³⁺, Mg²⁺, Ca²⁺, Cu²⁺ and Li⁺.